KEMANUSIAAN BARU: SEBUAH WACANA PENEGUHAN GAGASAN DALAM SILA KEDUA PANCASILA - Hari Zamharir; Sazali Sazali (Jurnal Ilmu dan Budaya, 2017)
Our current crisis of humanity should have also been associated with the problematic conception of humanity within secular or positivist social science perspective, especially with regards the ethics. The paper makes further account of the discourse on humanity in order to give light to better philosophical basis for our changes of world politics. The view would also contribute to encouraging discourse on the ideological basis of Indonesia, Pancasila.